Case Report: Safety and Efficacy of Tocilizumab in a Patient with Rheumatoid Arthritis and Chronic Hepatitis C - Filippo Iebba; Fiorella Di Sora; Agapito Tarasi; Wilma Leti; Tatiana Montella; Francesco Montella (Case Reports in Medicine)
Tocilizumab is a monoclonal humanized anti-IL-6-receptor antibody used for the treatment of rheumatoid arthritis. The safety of tocilizumab in HCV patients is an open question. We report on safety and efficacy of tocilizumab in a 71-year-old female with rheumatoid arthritis and chronic hepatitis C. Monotherapy with tocilizumab (8 mg/kg every 4 weeks, i.v.) was prescribed after the discontinuation, determined by clinical inefficacy, of anti-TNF-alfa agents (adalimumab and, subsequently, etanercept). We have registered an optimal and rapid clinical response to tocilizumab with early remission (SDAI <3.3 since 4 weeks). The safety was good with no adverse events and maintenance, during a six-month followup, of normal liver enzymes. These data suggest a good safety profile of tocilizumab in patients with rheumatoid arthritis and chronic hepatitis C virus pathology.